Cost-effectiveness of edaravone dexborneol versus edaravone for the treatment of acute ischemic stroke in China: Based on the TASTE study - Shi, Fenghao; He, Zixuan; Wang, Lin; Su, Hang; Han, Sheng (Frontiers in Pharmacology, 2022)
Background and Purpose: The TASTE Trial indicated that patients with acute ischemic stroke(AIS) using edaravone dexborneol have a significantly higher proportion of 90-day good functional outcomes (mRS0-1) than those using edaravone. This study compared the cost-effectiveness of the above interventions in treating AIS in the Chinese setting, aiming to inform treatment decisions in clinical practice. Methods: A model combing decision tree and markov model was developed to assess the cost-effectiveness of edaravone dexborneol versus edaravone for AIS over a 30-year time horizon from the Chinese healthcare system’s perspective. Both efficacy and safety data were extracted from the TASTE study. Local costs and utilities were derived from publications and open-access databases, both cost and effectiveness were discounted at a rate of 5% per year. Sensitivity analyses were conducted to ensure robustness and identify the main drivers of the result. Results: Compared with edaravone, edaravone dexborneol for AIS was found to be cost-effective in the first year and highly cost-effective as the study time horizons extended. In the long-term(30 years), edaravone dexborneol yielded a lifetime gain of 0.27(0.08-0.48) quality-adjusted life-years (QALY) at an additional cost of CNY 2099.57(-3445.24-6637.23), yielding an ICER of CNY 14603.83 per QALY gained under the willingness-to-pay (WTP)of 1.5 times per capita GDP (121,464 CNY). The result is robust in both deterministic and probabilistic sensitivity analysis (PSA), with the advantage of the edaravone dexborneol strategy increasing over time. Specifically, the probability of edaravone dexborneol dominant dexborneol is 85.2%, 99.0%, and 99.6% over 1 year, 5 years, and 30 years time horizons. Conclusion: Both short and long-term economic analyses suggest that edaravone dexborneol was highly likely to be a cost-effective alternative to treat AIS compared with edaravone in China. Expanding the use of edaravone dexborneol could lower healthcare expenditure in both the short and the long term.